Gambaran Waktu Pulih Sadar pada Pasien Post General Anestesi di Rumah Sakit Umum Emanuel Banjarnegara - Nofrysanti Lumba Ratu; Amin Susanto; Arlyana Hikmanti (Journal of Educational Innovation and Public Health, 2026)
General anesthesia is a commonly used anesthetic technique in various surgical procedures. One indicator of the success of anesthesia is the patient's recovery time after surgery. Recovery time can be influenced by several factors such as age, body mass index (BMI), type of surgery, and duration of surgery. This study aims to describe the recovery time of post-general anesthesia patients at Emanuel General Hospital, Banjarnegara. This study used a quantitative method with a descriptive design. The study sample consisted of 94 respondents selected using total sampling technique according to the inclusion criteria. Data collection was carried out using observation sheets and analyzed using descriptive statistical analysis. The results showed that most patients had a fast recovery time (≤15 minutes) as many as 89 respondents (94.7%), while patients with a recovery time of more than 15 minutes were 5 respondents (5.3%). Factors affecting recovery time in this study included age, body mass index, type of surgery, and duration of surgery. The conclusion of this study shows that most post-general anesthesia patients at Emanuel General Hospital, Banjarnegara have a fast recovery time.